Fundamental of Entrepreneurship ENT300 Magical Classic Burger / Eileen Richad... [et.al] - Richad, Eileen; Osman, Nur Farhana; Akau, Audreyza; Nambi, Rona; Temenggong, Anessia Devy (2014)
Our business is supremely focusing on customer's satisfaction and to provide a differ taste of burger which fit every customer taste bud and healthy. At Magical Classic Burger we are using only the fresh raw material and preparing the meals according to the Food Handling Department guideline. Our business will be operating from 10 am to 10 pm daily from Monday to Thursday but for weekend we will extend the business hours for another 2 hours, which make it from until 12 am. We also provide students card discount where students will enjoy the student price when they showing their student card during the certain period.